2013
DOI: 10.1002/joc.3684
|View full text |Cite
|
Sign up to set email alerts
|

Variations of surface temperature and rainfall in Vietnam from 1971 to 2010

Abstract: This study characterizes rainfall and temperature variability for the whole of Vietnam and for climate subregions over 40 years from 1971 to 2010. Vietnam's average temperature has increased at a rate of 0.26 ± 0.10 • C per decade since the 1970s, approximately twice the rate of global warming over the same period. The rate of increase is greater in winter than in summer. Except for the Central Highland, annual average temperatures in southern regions are increasing more rapidly than in the North. The increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 58 publications
11
89
2
3
Order By: Relevance
“…Chen et al (2012) suggested that the interannual variation of autumn rainfall in central Vietnam is influenced by rain-producing weather systems. Nguyen et al (2014) investigated rainfall and temperature variability for the whole of Vietnam from 1971 to 2010, revealing relationships between El Niño-Southern Oscillation (ENSO) and temperature and rainfall variability.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2012) suggested that the interannual variation of autumn rainfall in central Vietnam is influenced by rain-producing weather systems. Nguyen et al (2014) investigated rainfall and temperature variability for the whole of Vietnam from 1971 to 2010, revealing relationships between El Niño-Southern Oscillation (ENSO) and temperature and rainfall variability.…”
Section: Introductionmentioning
confidence: 99%
“…For the detailed example of Vietnam, 40 years (1971–2010) of daily observations from 60 stations over Vietnam are utilized. These 60 stations are well distributed throughout all subregions of Vietnam [ Nguyen et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…Precipitation amounts in the rainy season, which starts in May and ends in October are related to the migration of the monsoon over the continent. Due to Vietnam's geographic stretch from North to South, months with peak amounts of precipitation vary between provinces [15]. Winters are dominated by the East Asian monsoon.…”
Section: Climatic Settingmentioning
confidence: 99%
“…Winters are dominated by the East Asian monsoon. This monsoon is cold and dry and mainly impacts the North and Central Areas of Vietnam [15]. The Northern part of Vietnam receives the most precipitation in the summer, whereas the central part is characterized by a fall regime.…”
Section: Climatic Settingmentioning
confidence: 99%